Impact of Ascorbic acid and Potassium on Okra (Abelmoschus esculentus) Growth in Saline Condition - Sakar A. Saheed; Halala R. Qader (Zanco Journal of Pure and Applied Sciences, 2020)
Salinity regards as one of the abiotic stress factors affect that effect the growth and development of the plant. In present investigation the combination effect of ascorbic acid and potassium has been studies on okra growth under salt stress condition. The study conducted in factorial experiment of three replications in Completely Randomized Designed replicated three times. Three levels of potassium (K) (0,200, 400 ppm) applied to the soil. Three levels of foliar application of ascorbic acid (ASA) (0, 100, 200ppm). Irrigated with three levels of NaCl (0,100,200 µS). Parameters were recorded plant height (cm), number of leaves per plant, leaf area (cm2), water content (%), chlorophyll content, protein and proline content of leaves, mineral content; nitrogen, phosphorus, calcium, potassium, and sodium. The results elucidate that combination impact of ascorbic acid and potassium significantly the tolerance of okra plant to salinity due to an increase in height of plant, number of leaves, shoot water content, protein and proline content of leaves, and mineral contents such as nitrogen and sodium content of leaves under salt stress conditions.